THINKING A SUBSPACE FOR MAN: REFLECTIONS ON SOCIOSPATIAL PROBLEMS OF SMALL CITIES FROM THE MICROREGION OF UMARIZAL (RN) PENSANDO UM SUBESPAÇO DO HOMEM: REFLEXÕES SOBRE PROBLEMAS SOCIOESPACIAIS DAS PEQUENAS CIDADES DA MICRORREGIÃO DE UMARIZAL (RN) - José Erimar dos Santos; Rita de Cássia da Conceição Gomes; Maria José Costa Fernandes; Rosalvo Nobre Carneiro; Luiz Eduardo do Nascimento Neto (Geografia Ensino & Pesquisa, 2012)
We aim to reflect on the small towns of the Microregion of Umarizal, addressing some of the main issues in the context of urban geography. The methodological approach adopted focuses on issues concerning the economic and sociospatial aspects, considering specially the following dimensions: education, housing, employment, income and health. Where necessary we make reference to IBGE data, to the literature of the area and also to empirical experience. The results reveal that this microregion undergoes significant deficiencies related to social services, as well as the labor market and therefore spatial, related directly to the question problems and of stagnation relevant to the insignificant development itself and the planning of the spaces that constitutes it. Objetivamos refletir sobre as pequenas cidades da Microrregião de Umarizal, abordando algumas de suas principais problemáticas, no âmbito da geografia urbana. O recorte metodológico adotado privilegia questões de âmbito econômico e socioespacial referentes, sobretudo às dimensões: educacional, habitacional, emprego, renda e saúde recorrendo-se, quando necessário, aos dados do IBGE, pesquisa bibliográfica e experiência empírica. O trabalho permitiu perceber que a referida microrregião geográfica passa por significativas deficiências ligadas aos serviços sociais, bem como ao mercado de trabalho e, portanto, espaciais, vinculados diretamente às questões problemáticas e de estagnação pertinentes ao próprio insignificante desenvolvimento e planejamento dos espaços que a formam.